Accounting support for biofuel production in the context of Ukraine's sustainable development goals - I.V.; V.V.; V.A. (Економіка, управління та адміністрування)
The sphere of the charcoal industry is a practical implementation of the main provisions of the concept of sustainable development. Therefore, solving the priority problems related to this area are important steps towards the introduction of alternative energy sources, which will stop the depletion of traditional ones, as well as contribute to the preservation of the environment and human health. The development of this industry is important for the implementation of the Sustainable Development Goals, as among the most renewable energy sources are the most common energy sources of biological origin, which belong to those safe fuels, the use of which does not threaten the greenhouse effect. The purpose of the article is to substantiate the theoretical provisions and develop practical recommendations for improving the accounting of biofuel production to ensure the implementation of the Sustainable Development Goals. This aim requires a number of tasks, namely: the development of theoretical aspects of accounting for biofuel production in terms of sustainable development; improvement of organizational and methodological provisions of accounting for biofuel production as a means of implementing the Sustainable Development Goals of Ukraine. Research methods. General scientific and specific methods of cognition are used, in particular methods of deduction, induction, systematization and comparison, analysis and synthesis, as well as causal and abstract-logical methods. The role of accounting in information support of the Sustainable Development Goals is determined and the ideas of development of theoretical provisions and improvement of organization and methods of accounting of biofuel production are put forward, taking into account the need to harmonize economic, social and environmental activities of coal industry. Taking into account the peculiarities of the charcoal industry, the authors have improved the methodological support for accounting of operations for the production of biofuels (charcoal) in terms of developing the application of elements of the method of accounting: accounts - developed working plan of accounts for biofuels; developed double entry - the sequence of reflection in accounting of operations taking into account features of production of biofuel; calculation - outlined the set of costs for inclusion in the cost of production, proposed a procedure for the distribution of overhead costs; reporting - developed a form of Management Report on the production and sale of biofuels, which will quickly provide management with information on the volume and cost of biofuel production by type, as well as its implementation in domestic and foreign markets.